Investment Analysis Of The Masela Block Project. Will The Masela Block Become A Natural Resource Paradox? (A Pestle Analysis) - Sandanafu, Sally Paulina; Leuhery, Lenora; Wattimena, Sefnath J; Patty, Meidylisa (Jurnal Ilmu Sosial Mamangan, 2023)
The unsustainable investment in the Masela block due to the recent pandemic has delayed several steps by the Maluku provincial government and local communities in realizing the investment capital participation (PI). This study aims to determine and analyze the factors that hinder the operation and investment in the Masela block. The analysis technique used in this study is the PESTLE analysis which is reinforced by secondary data and survey results and interviews with PT MEA, namely the industry appointed by the local government (BUMD) in implementing the investment capital participation in the Masela block and informants from the Latdalam and Lermatang village governments who know and are directly affected by the development of the Masela Block project. The results of this study indicate that the priority concentration of the Lermatang and Latdalam village communities is on the social and environmental aspects where there will be many social changes in the community's way of life so that this aspect must be truly considered because these two villages highly uphold customary and cultural values and depend on natural resources.